👤

Bonsoir est ce que vous pouvez m’aider s’il vous plaît
Développer , réduire et ordonner les expressions
A = (x-y) ( x^{2} +xy+y^{2} )
B = ( 3x-2)(1-x) +3 (x+2)^{2}
C = ( x+y+1) (x-y-1)


Répondre :

A = (x-y)(x²+xy+y²) = x³+x²y+xy²-x²y-xy²-y³ = x³-y³

B = (3x-2)(1-x)+3(x+2)² = 3x-3x²-2+2x+3(x²+4x+4)
                                      = -3x²+3x²+3x+2x+12x-2+12
                                      = 17x+10

C = (x+y+1)(x-y-1) = x²-xy-x+xy-y²-y+x-y-1
                              = x²-y²-2y-1